Fetal bovine dermis as an alternative to allograft in large burn injuries - Soman Sen; Luke Hsei; Kathleen Romanowski; Tina Palmieri; David Greenhalgh (Elsevier, 2018)
Introduction: Dermal substitutes can be an essential treatment option for patients with very large burn injuries. We reviewed and compared our experience with a fetal bovine dermis dermal substitute versus allograft for adult burn patients with large burn injuries. Methods: After obtaining regulatory approval from our local institutional review board, we performed a 1 year retrospective review of adult burn patients with a TBSA of 50% or greater who underwent grafting with either fetal bovine dermis or allograft. We collected data that included age, TBSA, length of stay, number of operations,% area grafted with either allograft or fetal bovine dermis, and time between allograft or fetal bovine dermis grafting to autografting. All mean values are mean ± standard deviation, and all median values are median (interquartile range) Results: Overall for this review 15 patients met entry criteria. The mean age was 36 ± 9 years and mean TBSA was 71 ± 15%. Mean area grafted with either allograft (ALLO) or fetal bovine dermis (FBD) was 20 ± 8%. Mean time from grafting with ALLO or FB was 30 ± 12 days. There was no difference in median age between the ALLO group (30 (26-31)) and FBD group (35 (32-46) and there was no difference in median TBSA between the ALLO group (68(60-75)%) and FBD group (69(59-88)%). The median area grafted with allograft was 20(20-30)% which was not significantly different than the median area grafted with FBD (16.5(11-26)%). Additionally, there was no difference between the time from grafting with ALLO to autologous skin grafting (26(22-36) days) and the time from grafting with FBD to autologous skin grafting (25.5(21-32) days). Conclusions: Fetal bovine dermis is an acceptable alternative to allograft in patients with a large TBSA burn-injury. Further studies are needed to determine if infectious and functional outcomes are improved with fetal bovine dermis. Keywords: Dermal substitute, Fetal bovine dermis, Severe burn injury